2013
DOI: 10.1016/j.jval.2013.08.479
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Toxicities Associated with Advanced Melanoma Treatments in the United States

Abstract: Objectives: Prostate cancer (PCA) is the most common cancer in men worldwide. However, there is disagreement about the benefits of existing screening programs. This is mainly due to low specificity of currently utilized biomarkers. This can lead to both inappropriate medical treatment and increasing costs of care. For the future, many biotechnological developments are promising, but not all will be affordable for routine screening. The question is how much a complementary biomarker to prostate-specific antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…Additionally, the cost on the healthcare system is substantial with one study estimating the cost to be over $20,000 and 5 hospital days for inpatient hospitalization for severe episodes of colitis and diarrhea in the United States. 50 With the increasing use of immune checkpoint inhibitors (ICI) in oncology, there will be a concomitant rise in the incidence of immune-related colitis. This systematic review provides a basis to increase clinician awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the cost on the healthcare system is substantial with one study estimating the cost to be over $20,000 and 5 hospital days for inpatient hospitalization for severe episodes of colitis and diarrhea in the United States. 50 With the increasing use of immune checkpoint inhibitors (ICI) in oncology, there will be a concomitant rise in the incidence of immune-related colitis. This systematic review provides a basis to increase clinician awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing PEMBRO with IPI in controlled trials, PEMBRO as a single agent demonstrated prolonged progression-free and overall survival with fewer high-grade adverse events 6 , and NIVO administered in combination with IPI has better progression free survival and higher rates of objective response than with IPI alone 7 . Costs related to toxicity can be substantial, particularly with respect to inpatient management of AEs [11][12][13] . In clinical trials, reported grade 3 or 4 treatment-related adverse events (AEs) are 59% with IPI þ NIVO in combination and 17% with PEMBRO as a single agent 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of clearly-defined treatment algorithms is highlighted by the high incidence of hospitalization and complications from prolonged steroid tapers, which contribute to the financial toxicity of checkpoint inhibitor therapy. 26 Given its retrospective nature, the study has several limitations. First, while general guidelines are available to treat immune-related colitis, there are likely differences in practice patterns at each institution which may have affected treatment outcomes (e.g.…”
Section: Discussionmentioning
confidence: 99%